2014
DOI: 10.3109/10715762.2014.920086
|View full text |Cite
|
Sign up to set email alerts
|

Biological and metabolic response in STS-135 space-flown mouse skin

Abstract: There is evidence that space flight condition-induced biological damage is associated with increased oxidative stress and extracellular matrix (ECM) remodeling. To explore possible mechanisms, changes in gene expression profiles implicated in oxidative stress and in ECM remodeling in mouse skin were examined after space flight. The metabolic effects of space flight in skin tissues were also characterized. Space Shuttle Atlantis (STS-135) was launched at the Kennedy Space Center on a 13-day mission. Female C57B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(32 citation statements)
references
References 44 publications
2
26
0
Order By: Relevance
“…Consistent with our previous results in the liver and skin from these same mice where we found that spaceflight had a major impact on metabolism [33,[60][61][62], the next broad category involved to be impacted by spaceflight in the brain include glycolysis and metabolism.…”
Section: Consistent With the Upregulation Of Proteins Related To Neursupporting
confidence: 92%
“…Consistent with our previous results in the liver and skin from these same mice where we found that spaceflight had a major impact on metabolism [33,[60][61][62], the next broad category involved to be impacted by spaceflight in the brain include glycolysis and metabolism.…”
Section: Consistent With the Upregulation Of Proteins Related To Neursupporting
confidence: 92%
“…In support of this is the trend for a spaceflight-induced up-regulation of adrenal levels of corticosterone, an indicator of increased hypothalamus-pituitary-adrenal (HPA) activity. Metabolomic analysis of both the liver (presented here) and skin [54] of these mice showed similar increases in corticosterone levels. This is also generally consistent with reports of post-flight increases in circulating corticosterone levels in rodent models [7, 17, 26, 55].…”
Section: Discussionmentioning
confidence: 71%
“…Consistent with this hypothesis, the expression profiles of many different genes of human keratinocytes are affected under exposure to simulated microgravity in a time-dependent manner and during recovery 14 . In addition, it has been recently reported that long term exposure to microgravity conditions is able to affect mouse skin homeostasis 15, 16 , mostly inducing expression modulations of those genes responsible for remodeling of the extracellular matrix 15 and leading to dermal atrophy 16 : however, the physiological behaviour of the epidermal keratinocytes and their molecular pattern did not appear significantly altered in such environment 16 . Therefore, in the present paper, we searched for changes on the regenerative ability and response to tissue damage of human epidermal cells through the analysis of the effects of the simulated microgravity on the repair process.…”
Section: Introductionmentioning
confidence: 99%